Modern Sufism in Turkey: A Study of the Thought of Said Nursi and Fethullah Gulen - Ulil Albab, Muhammad; Nurwahidin, Nurwahidin (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
The advancement of technology and the development of time, in fact, don’t make sufism become deserted enthusiasts. Sufism is often considered an alternative way of embroidery in the modern era. This is inseparable from the fact that Islamic puritanism echoed by Salafi-Wahabi groups is considered to give birth to new humanitarian problems. Although it was also once considered a barrier in the progress of Islam by Modernists, it is undeniable that the need for sufism in society seems to never die. While in the Arab region the existence of sufism is threatened because it is considered contrary to the idea of Islamic puritanism and is considered a barrier in the progress of Islam, sufism in Turkey actually gets direct opposition from ultra-secular rulers. This makes sufi leaders in Turkey must transform the teachings of sufism. Through this article, the author seeks to display the patterns and approaches of a new sufism in Turkey, which came to be known as modern sufism. The authors base this study from the analysis of Said Nursi and Fethullah Gulen’s thoughts on sufism. The authors conclude that the pattern and approach of modern sufism in Turkey is carried out without tariqah. Nevertheless, the order transformed into an Islamic movement by adopting a state-legalized organization. It is also a form of adaptation carried out by sufi figures in Turkey as a measure of anticipation of the repressive actions of ultra-secular rulers against the followers of the order.